Diplomasi Budaya Inggris Melalui Grup Musik One Direction di Indonesia - Abdullah Azzam, Akmal; Setiawan, Asep (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2025)
This study explores the United Kingdom's cultural diplomacy through the boy band One Direction in Indonesia as a form of soft power implementation in international relations. Using a descriptive qualitative approach through literature review and content analysis, this research examines how One Direction serves as an effective instrument of cultural diplomacy by introducing British cultural values to Indonesian society. The 2015 "On the Road Again" concert in Jakarta is highlighted as a key event that illustrates how popular culture can enhance public sympathy toward a foreign nation. Phenomena such as the adoption of British slang, social practices like afternoon tea, and the active engagement of fans on social media demonstrate the success of One Direction in transmitting Britpop values. The study concludes that music-based cultural diplomacy has a significant impact on shaping a positive perception of the UK in Indonesia and strengthens bilateral relations between the two countries.  Keywords: cultural diplomacy, soft power, One Direction, United Kingdom, Indonesia, popular music.